(untitled) (Heritage, 2022)
The aim of the research was to determine the predictive power of parenting styles assessed by adolescents in predicting adolescent psychopathic tendencies. The sample consisted of 270 adolescents aged 16 and 17 attending one of four high schools in Kosovska Mitrovica. The following instruments were used in the research: Parenting Styles and Dimensions Questionnaire - PSDQ and Psychopathy Assessment Questionnaire - PAQ. The results of the research show that adolescents perceive their parents as predominantly authoritative in their upbringing and that they show low psychopathic tendencies. Father’s upbringing styles assessed by adolescents as a model explain 8% to 10% of variance in adolescent psychopathic tendencies, and regulation with a negative sign of the β coefficient as an aspect of authoritative upbringing style, and coercion and verbal hostility as aspects of authoritarian upbringing stand out as significant predictors. Maternal parenting styles assessed by adolescents as a model explain 5% to 8% of the variance in adolescent psychopathic tendencies, but no variable has emerged from the group of predictor variables as a significant predictor.